The role of intelligent transportation systems in solving traffic problems and reducing environmental negative impact of urban transport: . - Badi, Ibrahim; Bouraima, Mouhamed Bayane; Muhammad, L. J. (Decision Making and Analysis, 2022)
Information technology has produced many modern systems in the field of intelligent transportation systems that aim to integrate existing and new systems for the management of transportation and traffic networks to respond to changing (dynamic) traffic conditions. These systems have been applied in many Western countries for several purposes, the most important of which is traffic safety and the reduction of losses resulting from poor planning of these networks. Many transport systems in developing countries continue to suffer from many problems, such as high accident rates, traffic congestion, and pollution from car exhaust. This paper aims to use multi-criteria decision-making methods to help select the best technology to overcome the traffic problems in Libya. A hybrid model of Analytic Hierarchical Process (AHP) and the Measurement Alternatives and Ranking according to COmpromise Solution (MARCOS) method was used. The AHP method was used to determine the weights of six technologies for intelligent systems, with the results showing that the most appropriate technology was surveillance cameras, with a weight of 28%. The resulting weights were used to rank the impact of these technologies on safety, environment and efficiency. This study can help decision makers on selection of the best systems that can be used to overcome the current problems faced by the transportation system.